Overconfidence, financial literacy, and panic selling: Evidence from Japan - Aliyu Ali Bawalle; Mostafa Saidur Rahim Khan; Yoshihiko Kadoya (PLoS ONE, 2025)
This study investigates the phenomenon of panic selling, in which investors rapidly sell financial securities due to fear or uncertainty, often causing asset prices to plummet. Despite the significance of this behavior during market crises, there is limited understanding of the factors that drive panic selling. To address this gap, we applied the overreaction hypothesis, integrating financial literacy to explore whether investor sentiment influences trading decisions even when financial knowledge is present. We analyzed individual investor level data from a survey conducted by Rakuten Securities Company and Hiroshima University in Japan, covering the period between November and December 2023. Using probit regression models, we examined the relationship between panic selling, financial literacy, and overconfidence, while controlling for demographic, socioeconomic, and psychological factors. Our findings reveal that overconfident investors are more likely to engage in panic selling during market downturns, even when financial literacy reduces such tendencies. This relationship persists across various degrees of selling, including partial and full divestment of stocks and mutual funds. The results underscore the importance for policymakers to monitor the dissemination of negative information during crises to mitigate panic selling. At the household level, the findings highlight the need for investors to acquire financial knowledge and seek reliable information to make informed decisions, thereby reducing their susceptibility to panic selling.